2012
DOI: 10.1302/0301-620x.94b2.27914
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of medial and lateral meniscal transplantation with regard to extrusion of the allograft, and its correlation with clinical outcome

Abstract: We compared extrusion of the allograft after medial and lateral meniscal allograft transplantation and examined the correlation between the extent of extrusion and the clinical outcome. A total of 73 lateral and 26 medial meniscus allografts were evaluated by MRI at a mean of 32 months (24 to 59) in 99 patients (67 men, 32 women) with a mean age of 35 years (21 to 52). The absolute values and the proportional widths of extruded menisci as a percentage were measured in coronal images that showed maximum extrusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 35 publications
(47 reference statements)
1
48
0
1
Order By: Relevance
“…In previously reported studies, however, medial transplanted menisci were less extruded than lateral transplanted menisci. 15 We believe that our results have little bias because the nonexcision group had more MMATs than the excision group but showed more extrusion. Finally, osteophyte excision was not randomized, but it was initiated at a certain time point, which may induce selection bias.…”
Section: Discussionmentioning
confidence: 64%
“…In previously reported studies, however, medial transplanted menisci were less extruded than lateral transplanted menisci. 15 We believe that our results have little bias because the nonexcision group had more MMATs than the excision group but showed more extrusion. Finally, osteophyte excision was not randomized, but it was initiated at a certain time point, which may induce selection bias.…”
Section: Discussionmentioning
confidence: 64%
“…Open surgery is associated with less meniscal extrusion. Yoon et al 218 found more graft extrusion in the medial group on MRI, but Koh et al 219 observed that transplanted lateral menisci extruded more significantly than transplanted medial menisci. However, the clinical outcome after MAT was not found to be adversely affected by extrusion of the allograft.…”
Section: Results Of Meniscal Transplantsmentioning
confidence: 99%
“…Some aspects of the surgical technique, such as the way the graft is implanted and fixed (namely, soft tissue vs bony fixation),26 the type of allograft (medial vs lateral)68 and the sizing method,69 have been looked at. In a prospective series of 88 MATs comparing soft tissue fixation versus bony fixation, Abat el al 26 found a higher percentage of extruded meniscal tissue in the soft tissue fixation group.…”
Section: Allograft Extrusionmentioning
confidence: 99%
“…This suggested the superiority of bony fixation in terms of limiting extrusion. Koh et al 68 evaluated a series of 73 lateral and 26 medial meniscus allografts by means of MRI at a mean follow-up of 32 months. Their results showed that lateral MAT extrudes significantly more than the medial MAT.…”
Section: Allograft Extrusionmentioning
confidence: 99%